2002
DOI: 10.1046/j.1365-2958.2002.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene (lpt‐3) required for the addition of phosphoethanolamine to the lipopolysaccharide inner core of Neisseria meningitidis and its role in mediating susceptibility to bactericidal killing and opsonophagocytosis

Abstract: SummaryWe have identified a gene, lpt-3, that is required for the addition of phosphoethanolamine to the 3-position (PEtn-3) on the b-chain heptose (HepII) of the inner core lipopolysaccharide (LPS) of Neisseria meningitidis (Nm). The presence of this PEtn-3 substituent is characteristic of the LPS of a majority (ª 70%) of hypervirulent Nm strains, irrespective of capsular serogroup, and is required for the binding of a previously described monoclonal antibody (mAb B5) to a surface-accessible epitope. All stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 43 publications
(63 reference statements)
4
78
0
Order By: Relevance
“…S4) Influence of pEtN Modification on the N-Linked Glycoproteome-The observation of pEtN on multiple N-linked glycoproteins, several of which are known targets of the human humoral immune response (47,49,52), suggested a possible association with protein immunogenicity. This would also be consistent with studies showing that pEtN is an immunodominant modification of Neisseria meningitidis LOS (53). Coupled with the association of the C. jejuni N-linked glycan itself in reactivity to patient sera (54), we attempted to determine whether pEtN modification influenced immunoreactivity to C. jejuni proteins.…”
Section: Identification Of a Petn-modified N-linked Glycan Insupporting
confidence: 79%
See 1 more Smart Citation
“…S4) Influence of pEtN Modification on the N-Linked Glycoproteome-The observation of pEtN on multiple N-linked glycoproteins, several of which are known targets of the human humoral immune response (47,49,52), suggested a possible association with protein immunogenicity. This would also be consistent with studies showing that pEtN is an immunodominant modification of Neisseria meningitidis LOS (53). Coupled with the association of the C. jejuni N-linked glycan itself in reactivity to patient sera (54), we attempted to determine whether pEtN modification influenced immunoreactivity to C. jejuni proteins.…”
Section: Identification Of a Petn-modified N-linked Glycan Insupporting
confidence: 79%
“…The addition of pEtN to C. jejuni substrates by E. coli pEtN transferases does have precedent, as E. coli EptA is capable of modifying C. jejuni lipid A (15). It is unclear whether the addition of pEtN will have an influence on vaccine reactivity or efficiency; however, pEtN has been noted as an immunodominant epitope (53), and therefore, care must be taken to ensure glycoprotein vaccines derived from this system either do not display the pEtN moiety or that the pEtN-glycan is harmless to recipients, and immunological reactivity is minimal compared with the intended epitope. Alternatively, these concerns may be overcome by the generation of an E. coli CLM24 derivative, in which the genes encoding endogenous pEtN transferases have been removed to limit background addition of pEtN to glyco-conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we sought to produce MAbs that would react with inner core structures that did not require the presence of PEtn at either the 3 or 6 position of HepII. To this end, we immunized mice with the double mutant MC58 lpt3 galE strain, a strain known to be deficient in any addition of PEtn to HepII (24). Three hybridomas producing MAbs that did not require the presence of PEtn at HepII were established as a result of three fusions.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies of L3B5 reactivity, it was clear that two genes, lpt3 and lgtG, were critical in determining the structures of the inner core epitopes. The gene lpt3 codes for an LPS PEtn transferase that adds PEtn to position 3 of HepII and competes with lgtG, which encodes the enzyme that adds glucose (Glc) to position 3 of HepII (24). Whether lgtG is switched on or off depends on the number of cytidines in the homopolymeric tract that affects whether the gene is in or out of frame and therefore affects the nature and functionality of the translated product.…”
mentioning
confidence: 99%
“…For example, the LPS of pmrAB-constitutive mutants of S. enterica serovar Typhimurium and E. coli contains more of its heptose-pyrophosphate moiety capped by ethanolamine (264,468). The gene (lpt-3) responsible for the addition of the phosphoethanolamine moiety to a heptose residue in the core region of N. meningitidis was identified (392); it is a homolog of the lptA gene involved in the addition of the phosphoethanolamine to lipid A, described above. Schnaitman and Klena (594) reported that a tolC mutant of E. coli produced a similar LPS, with an increased content of pyrophosphorylethanolamine.…”
Section: Vol 67 2003 Molecular Basis Of Outer Membrane Permeabilitymentioning
confidence: 99%